Polyacid intercalation hydrotalcite aramid fiber coated lithium battery diaphragm and preparation method thereof

By combining polyacid intercalated hydrotalcite with aramid and coating onto the lithium battery separator, the problem of insufficient thermal stability of aramid-coated separator in the prior art is solved, and higher thermal stability and lower The heat shrinkage rate meets the market's demand for high-performance lithium battery diaphragms.

CN119153891AActive Publication Date: 2024-12-17YANTAI TAYHO ADVANCED MATERIALS RES INST CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411657472.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2024-12-17
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The thermal stability of existing aramid-coated lithium battery membranes is insufficient and cannot meet the growing market demand.

Method used

Polyacid intercalation hydrotalcite and aramid are combined with polyacid intercalation, polyacid intercalation hydrotalcite is prepared by peeling and recombination method, mixed with aramid slurry, coated onto the surface of the base film, and treated with solidification bath to improve the thermal stability of the membrane. .

Benefits of technology

It significantly improves the thermal stability of the lithium battery separator, reduces the heat shrinkage rate, and provides higher application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153891A_ABST
    Figure CN119153891A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery materials, in particular to a polyacid intercalation hydrotalcite aramid fiber coated lithium battery diaphragm and a preparation method thereof.The preparation method comprises the steps that polyacid intercalation hydrotalcite is prepared through a stripping and recombination method, specifically, hydrotalcite is added into formamide, violent stirring is conducted under protection of inert gas for stripping to obtain suspension liquid, and the suspension liquid is dried to obtain the polyacid intercalation hydrotalcite aramid fiber coated lithium battery diaphragm; centrifuging the suspension to obtain a stripped hydrotalcite sheet layer, then adding a polyacid aqueous solution into the stripped hydrotalcite sheet layer, stirring for self-assembly, and finally performing solid-liquid separation to obtain polyacid intercalated hydrotalcite; uniformly mixing the polyacid intercalated hydrotalcite with aramid fiber slurry to obtain polyacid intercalated hydrotalcite aramid fiber coating slurry; and coating the surface of a base membrane with the polyacid intercalation hydrotalcite aramid fiber coating slurry, passing through a coagulating bath, and drying to obtain the polyacid intercalation hydrotalcite aramid fiber coated lithium battery diaphragm. The lithium battery diaphragm has higher thermal stability, and the preparation method is simple and high in practicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm and a preparation method thereof, belonging to the technical field of lithium ion battery materials. Background Art

[0002] In recent years, with the rapid development of science and technology, energy crisis and environmental pollution problems have also followed one after another. As a green and renewable energy source, lithium-ion batteries have received widespread attention. Lithium-ion batteries are widely used in digital products, electric vehicles, energy storage and other fields due to their advantages such as high operating voltage, long cycle life and no memory effect. Among them, the diaphragm, as one of the four main materials in lithium-ion batteries, is particularly important to the performance of the battery, especially the safety performance, so higher requirements are placed on diaphragm products.

[0003] Aramid coated diaphragm has the advantages of high safety, wettability and oxidation resistance, and is a new type of high-end diaphragm product. Aramid coating can improve the thermal stability of the diaphragm, but it still cannot meet the growing market needs. Hydrotalcite is a new type of functional material with a two-dimensional layered structure. Since the interlayer anions of hydrotalcite are exchangeable, a variety of guest anions can be introduced between the layers to prepare intercalated hydrotalcite. Therefore, the intercalated hydrotalcite material can be selected to be compounded with aramid diaphragm to improve the thermal stability of the diaphragm. Chinese patent application CN114479654A discloses a method for preparing an organic intercalated hydrotalcite-aramid coating liquid and its application in the coating of lithium battery diaphragm. In the aramid polymerization process, an organic intercalated hydrotalcite is added to prepare a coating liquid. The diaphragm prepared by this method can improve the temperature resistance, but the ability of this method to improve the temperature resistance of the diaphragm is also limited. At present, the thermal stability requirements for aramid coated diaphragms are getting higher and higher, so it is of great value to provide lithium battery diaphragms with higher thermal stability. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm and a preparation method thereof. The lithium battery diaphragm has higher thermal stability, and the preparation method is simple and practical.

[0005] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery separator, the preparation method comprising: S1. Preparation of polyacid intercalated hydrotalcite: The polyacid intercalated hydrotalcite is prepared by exfoliation and recombination method: hydrotalcite is added to formamide, and vigorously stirred under the protection of inert gas to exfoliate to obtain a suspension, the suspension is centrifuged to obtain an exfoliated hydrotalcite sheet, and then a polyacid aqueous solution is added to the exfoliated hydrotalcite sheet and stirred to self-assemble, and finally the polyacid intercalated hydrotalcite is separated by solid-liquid separation; S2. Preparation of coating slurry: The polyacid intercalated hydrotalcite and the aramid slurry are uniformly mixed to obtain the polyacid intercalated hydrotalcite aramid coating slurry; S3. Diaphragm preparation: The polyacid intercalated hydrotalcite aramid coating slurry is coated on the surface of the base film, and then dried after passing through a coagulation bath to obtain a polyacid intercalated hydrotalcite aramid coating lithium battery diaphragm.

[0006] Furthermore, the hydrotalcite is at least one of nickel-cobalt hydrotalcite and magnesium-aluminum hydrotalcite.

[0007] Furthermore, the polyacid is any one of a Keggin-type polyacid and a Weakley-type polyacid.

[0008] Furthermore, the solid content of the suspension is 1-3%.

[0009] Furthermore, the concentration of the polyacid aqueous solution is 5-15 mmol / L, and the mass ratio of the hydrotalcite to the polyacid is 1:(1-4).

[0010] Furthermore, in step S1, the vigorous stirring speed during preparation of the suspension is 1500-2000 r / min, and the vigorous stirring time is 24-48h; during self-assembly, the stirring speed is 800-1200 r / min, and the stirring time is 12-24h.

[0011] Furthermore, the aramid slurry is para-aramid slurry or meta-aramid slurry, and the solid content of the aramid slurry is 5%-10%; The mass content of the polyacid intercalated hydrotalcite in the coating slurry is 1%-3%.

[0012] Furthermore, in step S3, the coating thickness of the polyacid intercalated hydrotalcite aramid coating slurry is 1-2 μm.

[0013] Furthermore, the coagulation bath is a two-stage coagulation bath, the first stage coagulation bath is a mixed solution of DMAC and water, the water volume content in the first stage coagulation bath is 50-60%; the second stage coagulation bath is a mixed solution of DMAC and water, the water volume content in the second stage coagulation bath is 75-85%.

[0014] Furthermore, the difference in water volume content between the first-stage coagulation bath and the second-stage coagulation bath is not higher than 25%.

[0015] The invention also discloses a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm, and the polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm is prepared according to the preparation method of the invention.

[0016] The beneficial effects of the present invention are: The preparation method of the present invention introduces polyacid intercalated hydrotalcite into the membrane coating layer. Since the particle size of the polyacid intercalated hydrotalcite is nanometer-scale, the introduction of the polyacid intercalated hydrotalcite will not change the original morphology and thickness of the coating layer. In addition, the unique layered structure of the hydrotalcite and the stable embedding of the polyacid can enhance the thermal stability of the membrane. The present invention selects the stripping and recombination method to prepare the polyacid intercalated hydrotalcite, which can reduce the steric hindrance in the intercalation and recombination process, reduce the impurity phase, and improve the performance of the polyacid intercalated hydrotalcite. The polyacid intercalated hydrotalcite is introduced into the lithium battery membrane, which reduces the thermal shrinkage of the membrane and improves the thermal stability of the membrane, and has extremely high application value.

[0017] In the preparation method of the present invention, a lithium battery separator is prepared by introducing polyacid intercalated hydrotalcite into the separator coating layer, and suitable stripping and reorganization and coagulation bath conditions are combined to finally obtain a separator product with better thermal stability. The polyacid intercalated hydrotalcite is combined with aramid fiber through intermolecular forces, thereby improving the thermal stability of the aramid coated lithium battery separator. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a scanning electron microscope image of the polyacid intercalated hydrotalcite aramid coated lithium battery separator of Example 1; Figure 2 This is a comparison chart of the thermal shrinkage test of Example 1 and Comparative Example 1 before and after heating. DETAILED DESCRIPTION

[0019] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0021] A method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm, the preparation method comprising: S1. Preparation of polyacid intercalated hydrotalcite: The polyacid intercalated hydrotalcite is prepared by exfoliation and recombination method: hydrotalcite is added to formamide, and vigorously stirred under the protection of inert gas to exfoliate to obtain a suspension, the suspension is centrifuged to obtain an exfoliated hydrotalcite sheet, and then the polyacid aqueous solution is added to the exfoliated hydrotalcite sheet and stirred to self-assemble, and finally centrifuged, washed, and dried to obtain the polyacid intercalated hydrotalcite; S2. Preparation of coating slurry: The polyacid intercalated hydrotalcite and the aramid slurry are uniformly mixed to obtain the polyacid intercalated hydrotalcite aramid coating slurry; S3. Diaphragm preparation: The polyacid intercalated hydrotalcite aramid coating slurry is coated on the surface of the base film, and then dried after passing through a coagulation bath to obtain a polyacid intercalated hydrotalcite aramid coating lithium battery diaphragm.

[0022] Specifically, the hydrotalcite is at least one of nickel-cobalt hydrotalcite and magnesium-aluminum hydrotalcite.

[0023] Specifically, the polyacid is any one of a Keggin-type polyacid and a Weakley-type polyacid.

[0024] More specifically, the polyacid used in the embodiment of the present invention is phosphotungstic acid.

[0025] Specifically, the solid content in the suspension is 1-3% (mass content).

[0026] Specifically, the concentration of the polyacid aqueous solution is 5-15 mmol / L, and the mass ratio of the hydrotalcite to the polyacid is 1:(1-4).

[0027] More specifically, the vigorous stirring speed during the preparation of the suspension is 1500-2000 r / min, and the vigorous stirring time is 24-48h; during the self-assembly, the stirring speed is 800-1200 r / min, and the stirring time is 12-24h. When preparing the suspension, vigorous stirring is conducive to the smooth exfoliation of the hydrotalcite. When self-assembly is performed, the stirring speed is appropriately reduced to ensure the uniformity of the system while avoiding the breakage of the hydrotalcite sheet layer, and finally obtain an excellent polyacid intercalated hydrotalcite, which is more conducive to the application in the separator.

[0028] Specifically, the aramid slurry is para-aramid slurry or meta-aramid slurry, and the solid content of the aramid slurry is 5%-10%; in the embodiment of the present invention, the solvent in the aramid slurry is DMAC.

[0029] The mass content of the polyacid intercalated hydrotalcite in the coating slurry is 1%-3%.

[0030] Specifically, in step S3, the coating thickness of the polyacid intercalated hydrotalcite aramid coating slurry is 1-2 μm, and the coating is double-sided coating or single-sided coating.

[0031] More specifically, the coating method of step S3 may be spray coating, roller coating or scraping, etc. The coating method used in the embodiment of the present invention is scraping, but it is not a limitation of the present invention.

[0032] Specifically, the coagulation bath is a two-stage coagulation bath, the first stage coagulation bath is a mixed solution of DMAC and water, the water volume content in the first stage coagulation bath is 50-60%; the second stage coagulation bath is a mixed solution of DMAC and water, the water volume content in the second stage coagulation bath is 75-85%.

[0033] Specifically, the difference in water volume content between the first-stage coagulation bath and the second-stage coagulation bath is no more than 25%.

[0034] More specifically, the coagulation baths in the embodiments of the present invention are all at room temperature.

[0035] Specifically, the drying temperature in step S3 is 55-65°C.

[0036] Specifically, the base film material is an organic polymer base film, including polyethylene, polypropylene, polytetrafluoroethylene, etc. The base film is a dry or wet diaphragm, and the base film thickness can be 5-13 μm. The base film used in the embodiment of the present invention is a PE base film purchased from Xingyuan Materials, but this is not a limitation of the present invention.

[0037] A polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm is prepared according to the preparation method of the present invention.

[0038] Example 1 A method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm, the preparation method comprising: S1. Preparation of polyacid intercalated hydrotalcite: The polyacid intercalated hydrotalcite was prepared by exfoliation and recombination method: magnesium aluminum hydrotalcite was added to formamide, and exfoliated by vigorous stirring under nitrogen protection to obtain a suspension with a solid content of 2%; the vigorous stirring speed was 1500 r / min, and the vigorous stirring time was 48h; The suspension was centrifuged to obtain exfoliated hydrotalcite sheets, and then the phosphotungstic acid aqueous solution was added to the exfoliated hydrotalcite sheets and stirred for self-assembly, and finally centrifuged, washed and dried to obtain polyacid intercalated hydrotalcite; wherein the concentration of the phosphotungstic acid aqueous solution was 7mmol / L, the mass ratio of magnesium aluminum hydrotalcite to phosphotungstic acid was 1:1, the stirring speed during self-assembly was 1000 r / min, and the stirring time was 24h.

[0039] S2. Preparation of coating slurry: The polyacid intercalated hydrotalcite and aramid slurry are uniformly mixed to obtain a polyacid intercalated hydrotalcite aramid coating slurry; wherein the aramid slurry is a para-aramid slurry with a solid content of 8%, and the mass content of the polyacid intercalated hydrotalcite in the coating slurry is 3%.

[0040] S3. Diaphragm preparation: Take a PE base film with a thickness of 7 μm, cut it into a size of 30*50 cm, take an appropriate amount of slurry on the surface of the base film with a scraper to coat the diaphragm on both sides, the coating thickness is 2 μm, pass through a two-stage coagulation bath, and dry at 60°C to obtain a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm; The first coagulation bath is a mixed solution of DMAC and water, and the water volume content in the first coagulation bath is 55%; the second coagulation bath is a mixed solution of DMAC and water, and the water volume content in the second coagulation bath is 80%.

[0041] Example 2 A method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm, the preparation method comprising: S1. Preparation of polyacid intercalated hydrotalcite: Polyacid intercalated hydrotalcite was prepared by exfoliation and recombination method: nickel-cobalt hydrotalcite was added to formamide, and exfoliated by vigorous stirring under nitrogen protection to obtain a suspension with a solid content of 1%; the vigorous stirring speed was 2000 r / min, and the vigorous stirring time was 48h; The suspension was centrifuged to obtain exfoliated hydrotalcite sheets, and then the phosphotungstic acid aqueous solution was added to the exfoliated hydrotalcite sheets and stirred for self-assembly, and finally centrifuged, washed and dried to obtain polyacid intercalated hydrotalcite; wherein the concentration of the phosphotungstic acid aqueous solution was 12mmol / L, the mass ratio of magnesium aluminum hydrotalcite to phosphotungstic acid was 1:3.5, the stirring speed during self-assembly was 1200 r / min, and the stirring time was 24h.

[0042] S2. Preparation of coating slurry: The polyacid intercalated hydrotalcite and aramid slurry are uniformly mixed to obtain a polyacid intercalated hydrotalcite aramid coating slurry; wherein the aramid slurry is a para-aramid slurry with a solid content of 5%, and the mass content of the polyacid intercalated hydrotalcite in the coating slurry is 1%.

[0043] S3. Diaphragm preparation: Take a 9 μm thick PE base film, cut it into a size of 30*50 cm, take an appropriate amount of slurry on the surface of the base film with a scraper to coat the diaphragm on both sides, the coating thickness is 1 μm, pass through a two-stage coagulation bath, and dry at 60°C to obtain a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm; The first coagulation bath is a mixed solution of DMAC and water, and the water volume content in the first coagulation bath is 50%; the second coagulation bath is a mixed solution of DMAC and water, and the water volume content in the second coagulation bath is 75%.

[0044] Example 3 A method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm, the preparation method comprising: S1. Preparation of polyacid intercalated hydrotalcite: The polyacid intercalated hydrotalcite was prepared by exfoliation and recombination method: magnesium aluminum hydrotalcite was added to formamide, and exfoliated by vigorous stirring under nitrogen protection to obtain a suspension with a solid content of 3%; the vigorous stirring speed was 2000 r / min, and the vigorous stirring time was 48h; The suspension was centrifuged to obtain exfoliated hydrotalcite sheets, and then the phosphotungstic acid aqueous solution was added to the exfoliated hydrotalcite sheets and stirred for self-assembly, and finally centrifuged, washed and dried to obtain polyacid intercalated hydrotalcite; wherein the concentration of the phosphotungstic acid aqueous solution was 15mmol / L, the mass ratio of magnesium aluminum hydrotalcite to phosphotungstic acid was 1:2.5, the stirring speed during self-assembly was 1200 r / min, and the stirring time was 12h.

[0045] S2. Preparation of coating slurry: The polyacid intercalated hydrotalcite and aramid slurry are uniformly mixed to obtain a polyacid intercalated hydrotalcite aramid coating slurry; wherein the aramid slurry is a meta-aramid slurry with a solid content of 5%, and the mass content of the polyacid intercalated hydrotalcite in the coating slurry is 2%.

[0046] S3. Diaphragm preparation: Take a PE base film with a thickness of 7 μm, cut it into a size of 30*50 cm, take an appropriate amount of slurry on the surface of the base film with a scraper to coat the diaphragm on both sides, the coating thickness is 2 μm, pass through a two-stage coagulation bath, and dry at 60°C to obtain a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm; The first coagulation bath is a mixed solution of DMAC and water, and the water volume content in the first coagulation bath is 60%; the second coagulation bath is a mixed solution of DMAC and water, and the water volume content in the second coagulation bath is 85%.

[0047] Example 4 A method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm, the preparation method comprising: S1. Preparation of polyacid intercalated hydrotalcite: The polyacid intercalated hydrotalcite was prepared by exfoliation and recombination method: magnesium aluminum hydrotalcite was added to formamide, and exfoliated by vigorous stirring under nitrogen protection to obtain a suspension with a solid content of 2%; the vigorous stirring speed was 1500 r / min, and the vigorous stirring time was 24h; The suspension was centrifuged to obtain exfoliated hydrotalcite sheets, and then the phosphotungstic acid aqueous solution was added to the exfoliated hydrotalcite sheets and stirred for self-assembly, and finally centrifuged, washed and dried to obtain polyacid intercalated hydrotalcite; wherein the concentration of the phosphotungstic acid aqueous solution was 5mmol / L, the mass ratio of magnesium aluminum hydrotalcite to phosphotungstic acid was 1:2, the stirring speed during self-assembly was 800 r / min, and the stirring time was 24h.

[0048] S2. Preparation of coating slurry: The polyacid intercalated hydrotalcite and aramid slurry are uniformly mixed to obtain a polyacid intercalated hydrotalcite aramid coating slurry; wherein the aramid slurry is a meta-aramid slurry with a solid content of 7%, and the mass content of the polyacid intercalated hydrotalcite in the coating slurry is 1.5%.

[0049] S3. Diaphragm preparation: Take a PE base film with a thickness of 7 μm, cut it into a size of 30*50 cm, take an appropriate amount of slurry on the surface of the base film with a scraper to coat the diaphragm on both sides, the coating thickness is 2 μm, pass through a two-stage coagulation bath, and dry at 60°C to obtain a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm; The first coagulation bath is a mixed solution of DMAC and water, and the water volume content in the first coagulation bath is 50%; the second coagulation bath is a mixed solution of DMAC and water, and the water volume content in the second coagulation bath is 75%.

[0050] Comparative Example 1 The lithium battery separator was prepared by the same method as in Example 1, except that the polyacid intercalated hydrotalcite was not added, and the aramid slurry was directly coated on the base film. The specific preparation process is as follows: S1. Preparation of coating slurry: Aramid slurry is used as coating slurry, wherein the aramid slurry is para-aramid slurry with a solid content of 8%; S2. Diaphragm preparation: Take a PE base film with a thickness of 7 μm, cut it into a size of 30*50 cm, take an appropriate amount of slurry on the surface of the base film with a scraper to coat the diaphragm on both sides, the coating thickness is 2 μm, pass through a two-stage coagulation bath, and dry at 60°C to obtain a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm; The first coagulation bath is a mixed solution of DMAC and water, and the water volume content in the first coagulation bath is 55%; the second coagulation bath is a mixed solution of DMAC and water, and the water volume content in the second coagulation bath is 80%.

[0051] Comparative Example 2 The lithium battery separator was prepared by the same method as in Example 2, except that the polyacid intercalated hydrotalcite was not added, and the aramid slurry was directly coated on the base film. The specific preparation process is as follows: S1. Preparation of coating slurry: Aramid slurry is used as coating slurry, wherein the aramid slurry is para-aramid slurry with a solid content of 5%; S3. Diaphragm preparation: Take a 9 μm thick PE base film, cut it into a size of 30*50 cm, take an appropriate amount of slurry on the surface of the base film with a scraper to coat the diaphragm on both sides, the coating thickness is 1 μm, pass through a two-stage coagulation bath, and dry at 60°C to obtain a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm; The first coagulation bath is a mixed solution of DMAC and water, and the water volume content in the first coagulation bath is 50%; the second coagulation bath is a mixed solution of DMAC and water, and the water volume content in the second coagulation bath is 75%.

[0052] Comparative Example 3 The polyacid intercalated hydrotalcite was prepared with reference to Chinese patent CN101898155B, and the coating was carried out according to the coating method of Example 1 to obtain the polyacid intercalated hydrotalcite aramid coated diaphragm. The specific preparation process is as follows: S1. Preparation of polyacid intercalated hydrotalcite: The polyacid intercalated hydrotalcite was prepared according to the method of Example 1 of Chinese Patent CN101898155B; S2. Preparation of coating slurry: The polyacid intercalated hydrotalcite and aramid slurry are uniformly mixed to obtain a polyacid intercalated hydrotalcite aramid coating slurry; wherein the aramid slurry is a para-aramid slurry with a solid content of 8%, and the mass content of the polyacid intercalated hydrotalcite in the coating slurry is 3%.

[0053] S3. Diaphragm preparation: Take a PE base film with a thickness of 7 μm, cut it into a size of 30*50 cm, take an appropriate amount of slurry on the surface of the base film with a scraper to coat the diaphragm on both sides, the coating thickness is 2 μm, pass through a two-stage coagulation bath, and dry at 60°C to obtain a polyacid intercalated hydrotalcite aramid coated lithium battery diaphragm; The first coagulation bath is a mixed solution of DMAC and water, and the water volume content in the first coagulation bath is 55%; the second coagulation bath is a mixed solution of DMAC and water, and the water volume content in the second coagulation bath is 80%.

[0054] Comparative Example 4 The lithium battery separator was prepared by the same method as in Example 1, except that in step S1, the concentration of the phosphotungstic acid aqueous solution was increased, and the concentration of the phosphotungstic acid aqueous solution in this comparative example 4 was 20 mmol / L. The other process conditions were exactly the same as in Example 1.

[0055] Comparative Example 5 The lithium battery separator was prepared by the same method as in Example 1, except that in step S1, the concentration of the phosphotungstic acid aqueous solution was reduced, and the concentration of the phosphotungstic acid aqueous solution in this comparative example 5 was 2 mmol / L. The other process conditions were exactly the same as in Example 1.

[0056] Comparative Example 6 The lithium battery separator was prepared by the same method as in Example 1, except that in step S1, the amount of phosphotungstic acid was increased, and in this comparative example 6, the mass ratio of magnesium aluminum hydrotalcite to phosphotungstic acid was 1:5. The other process conditions were exactly the same as in Example 1.

[0057] Comparative Example 7 The lithium battery separator was prepared by the same method as in Example 1, except that in step S1, the amount of phosphotungstic acid was reduced, and in this comparative example 7, the mass ratio of magnesium aluminum hydrotalcite to phosphotungstic acid was 1:0.5. The other process conditions were exactly the same as in Example 1.

[0058] Comparative Example 8 The lithium battery separator was prepared by the same method as in Example 1, except that in step S2, the addition ratio of the polyacid intercalated hydrotalcite was increased, and the content of the polyacid intercalated hydrotalcite in the coating slurry in this comparative example 8 was 5%.

[0059] Comparative Example 9 The lithium battery separator was prepared by the same method as in Example 1, except that in step S3, the coagulation bath had only one level of coagulation bath, and the water volume content in the coagulation bath in this comparative example 9 was 80%.

[0060] Comparative Example 10 The lithium battery separator was prepared by the same method as in Example 1, except that: in step S3, the difference in water volume content between the first coagulation bath and the second coagulation bath was greater than 25%. In this comparative example 10, the water volume content in the first coagulation bath was 55%; the second coagulation bath was a mixed solution of DMAC and water, and the water volume content in the second coagulation bath was 85%.

[0061] The performance of the lithium battery separators prepared in the above examples and comparative examples was tested, wherein the test method is: the thickness and thermal shrinkage of the samples were tested with reference to the GB / T 36363-2018 standard. The specific test results are shown in Table 1 below.

[0062] Table 1 Lithium battery diaphragm performance test data

[0063] Note: MD in Table 1 stands for longitudinal direction and TD stands for transverse direction.

[0064] It can be seen from the above data that the lithium battery separators prepared by the preparation method of the present invention in Examples 1-4 have excellent thermal stability. The polyacid intercalated hydrotalcite is combined with the aramid fiber through intermolecular forces. The unique layered structure of the hydrotalcite and the stable embedding of the polyacid can improve the thermal stability of the aramid coating film. The thermal stability of the separator can be enhanced. Through the thermal shrinkage and film rupture temperature tests of the comparative examples and the embodiments, the introduction of the polyacid intercalated hydrotalcite reduces the thermal shrinkage rate of the separator and improves the thermal stability of the separator, which has a very high application value. In addition, since the particle size of the polyacid intercalated hydrotalcite is nanometer-scale, the introduction of the polyacid intercalated hydrotalcite will not change the original morphology and thickness of the coating layer. Figure 1 It can be clearly seen.

[0065] From the comparison of the data of Comparative Example 1-2 and Example 1-2, it can be seen that if the polyacid intercalated hydrotalcite is not added, the thermal stability of the lithium battery separator is significantly reduced. Figure 2 It can also be seen intuitively.

[0066] From the comparison of the data of Comparative Example 3 and Example 1, it can be seen that the polyacid intercalated hydrotalcite prepared by the preparation method of the present invention is more conducive to application in coating slurry, and finally obtains a lithium battery separator with excellent thermal stability. Because compared with other preparation methods of polyacid intercalated hydrotalcite, the exfoliation and recombination method can destroy the hydrogen bond network structure of hydrotalcite during the exfoliation process, reduce the interaction force between the sheets, facilitate the insertion of polyacids between the sheets, and reduce the generation of impurities.

[0067] From the data comparison of Comparative Examples 4-5 and Example 1, it can be seen that: the concentration of the phosphotungstic acid aqueous solution is too high or too low, which will affect the thermal stability of the lithium battery separator. When the concentration of the phosphotungstic acid aqueous solution is too low, the intercalation process is relatively slow, and the intercalation amount is limited, because the low-concentration polyacid molecules are difficult to fully enter the interlayer structure of the hydrotalcite, so that the thermal stability of the lithium battery separator is not high; if the concentration of the phosphotungstic acid aqueous solution is too high, the polyacid molecules cannot be evenly distributed between the layers, which may lead to incomplete intercalation or the formation of a mixed phase. The polyacid molecules with too high a concentration may destroy the balance between the hydrotalcite layers, resulting in an unstable structure, and ultimately reduce the thermal stability of the lithium battery separator. Therefore, the polyacid aqueous solution concentration defined by the present invention is more conducive to obtaining a lithium battery separator with excellent performance.

[0068] From the comparison of the data of Comparative Examples 6-7 and Example 1, it can be seen that the thermal stability of the lithium battery separator will be affected by reducing or increasing the proportion of phosphotungstic acid. When the proportion of phosphotungstic acid is too small, the self-assembly of hydrotalcite and polyacid is relatively small, and the intercalation amount is insufficient, so that the thermal stability of the lithium battery separator is not high; if the proportion of phosphotungstic acid is too high, too many polyacid molecules will be crowded between the layers, affecting the stability of the intercalation structure, and ultimately the thermal stability of the lithium battery separator will also decrease. Therefore, the polyacid aqueous solution concentration defined by the present invention is more conducive to obtaining a lithium battery separator with excellent performance.

[0069] From the comparison of the data of Comparative Example 8 and Example 1, it can be seen that if the amount of polyacid intercalated hydrotalcite in the coating slurry is too much, too many polyacid intercalated hydrotalcite particles will affect the structural stability of the aramid fiber, and the interaction between the polyacid intercalated hydrotalcite and aramid may be weakened due to the excessively high ratio, which will also lead to a decrease in the thermal stability of the lithium battery separator.

[0070] From the comparison of the data of Comparative Examples 9-10 and Example 1, it can be seen that the coagulation bath conditions defined in the present invention are more conducive to controlling the coagulation speed, so that the polyacid intercalated hydrotalcite is evenly distributed in the lithium battery separator, and finally a lithium battery separator with excellent thermal stability is obtained. If the coagulation bath concentration is not appropriate, it will affect the uniformity of the polyacid intercalated hydrotalcite, and finally lead to a decrease in the thermal stability of the lithium battery separator.

[0071] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0072] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery separator, characterized in that: The preparation method is: S1. Preparation of polyacid intercalated hydrotalcite: The polyacid intercalated hydrotalcite is prepared by exfoliation and recombination method: hydrotalcite is added to formamide, and vigorously stirred under the protection of inert gas to exfoliate to obtain a suspension, the suspension is centrifuged to obtain an exfoliated hydrotalcite sheet, and then a polyacid aqueous solution is added to the exfoliated hydrotalcite sheet and stirred to self-assemble, and finally the polyacid intercalated hydrotalcite is separated by solid-liquid separation; S2. Preparation of coating slurry: The polyacid intercalated hydrotalcite and the aramid slurry are uniformly mixed to obtain the polyacid intercalated hydrotalcite aramid coating slurry; S3. Diaphragm preparation: The polyacid intercalated hydrotalcite aramid coating slurry is coated on the surface of the base film, and then dried after passing through a coagulation bath to obtain a polyacid intercalated hydrotalcite aramid coating lithium battery diaphragm.

2. The method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery separator according to claim 1, characterized in that: The hydrotalcite is at least one of nickel-cobalt hydrotalcite and magnesium-aluminum hydrotalcite; and the polyacid is any one of Keggin-type polyacid and Weakley-type polyacid.

3. The method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery separator according to claim 1, characterized in that: The solid content in the suspension is 1-3%.

4. The method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery separator according to claim 1, characterized in that: The concentration of the polyacid aqueous solution is 5-15 mmol / L, and the mass ratio of the hydrotalcite to the polyacid is 1:(1-4).

5. The method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery separator according to claim 1, characterized in that: In step S1, the vigorous stirring speed when preparing the suspension is 1500-2000 r / min, and the vigorous stirring time is 24-48h; when performing self-assembly, the stirring speed is 800-1200 r / min, and the stirring time is 12-24h.

6. The method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery separator according to claim 1, characterized in that: The aramid slurry is para-aramid slurry or meta-aramid slurry, and the solid content of the aramid slurry is 5%-10%; The mass content of the polyacid intercalated hydrotalcite in the coating slurry is 1%-3%.

7. The method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery separator according to claim 1, characterized in that: In step S3, the coating thickness of the polyacid intercalated hydrotalcite aramid coating slurry is 1-2 μm.

8. The method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery separator according to claim 1, characterized in that: The coagulation bath is a two-stage coagulation bath, wherein the first-stage coagulation bath is a mixed solution of DMAC and water, wherein the volume content of water in the first-stage coagulation bath is 50-60%; and the second-stage coagulation bath is a mixed solution of DMAC and water, wherein the volume content of water in the second-stage coagulation bath is 75-85%.

9. The method for preparing a polyacid intercalated hydrotalcite aramid coated lithium battery separator according to claim 8, characterized in that: The difference in water volume content between the first-stage coagulation bath and the second-stage coagulation bath is not higher than 25%.

10. A polyacid intercalated hydrotalcite aramid coated lithium battery separator, characterized in that: The polyacid intercalated hydrotalcite aramid coated lithium battery separator is prepared according to the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Nonaqueous electrolyte battery, positive electrode for nonaqueous electrolyte battery, negative electrode for nonaqueous electrolyte battery, separator for nonaqueous electrolyte battery, electrolyte for nonaqueous electrolyte battery, and method for

    CN102460787A

  • Lithium ion battery composite diaphragm and preparation method thereof

    CN114243217A

  • Preparation method of organic intercalation hydrotalcite-aramid fiber coating liquid and application of organic intercalation hydrotalcite-aramid fiber coating liquid in lithium battery diaphragm coating

    CN114479654A

  • Polymer-metal compound composite ink and preparation method and use thereof

    EP3623426A1

  • Coated separator for lithium ion battery and method for preparing same

    EP4160804A1